Sistem Pendidikan Nasional di Pondok Pesantren - Nurresa Fi Sabil Resya; Fery Diantoro (IAIN PAREPARE, 2021)
Many teenagers do not continue school or drop out of school because of a lack of awareness of the importance of education, even though in the national education system one of the latest educational programs in the country is